A Study and Compare the Futuristic Thinking of Grade 9 Students in Schools of Different Sizes - Songsak Phusee-orn; Sasipat Pongteerawut (Journal of Educational Issues, 2024)
The research aimed at studying and comparing the futuristic thinking of Grade 9 students studying in schools of different sizes. The samples of the research were Grade 9 students of semester 2 in academic year 2020 in Sisaket Province, Thailand. The multi-stage random sampling technique was employed for the selection of 860 students from 12 schools: 216 students were from extra-large-sized, 160 from large-sized, 302 from medium-sized, and 182 from small-sized schools. The instrument used in the research was a 15 item-5-point Likert scale futuristic test. The validity (IOC) ranged from 0.32 to 0.75, Item Total Correlation from 0.57 to 0.75, and reliability value was 0.94. The data was analyzed using Mean, Standard Deviation (S.D.), One way ANOVA, and Scheffe’ method. The results showed that 1) Grade 9 students’ futuristic thinking was at high level in both overall and individual aspect; 2) Grade 9 students studying in schools of different sizes had different levels of futuristic thinking at the .05 level of statistical significance. Students from extra-large-sized schools had higher level of futuristic thinking than those from medium-sized ones. For those students who were in large schools had higher futuristic thinking levels than the ones in medium and small-sized schools, with a statistical significance of .05 level. The other pairs were not different.